Modifikasi Air Conditioner Split PK Sebagai Water Heater Untuk Media Pembelajaran Mesin Konversi Energi Bagi Mahasiswa Program Studi Teknik Mesin Universitas Muhammadiyah Pontianak - To, Gunarto; Julianto, Eko; Iwan, Muhammad; Sarwono, Eko (Universitas Muhammadiyah Metro, 2023)
AbstractThe purpose of this research is to modify PK Split Air Conditioner for water heater by utilizing condenser exhaust heat that can be used by students of Mechanical Engineering Study Program, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Pontianak as a learning media in the field of fluid machinery and laboratory-scale energy conversion machines. This design is important as an effort to increase students' learning motivation, understanding, and thinking skills in the energy conversion machine course, especially air conditioners. The research process involves designing, manufacturing, modifying, and assembling the air conditioner into a water heater into a complete unit, as well as testing the tool for use as a learning medium. Data collection and analysis are carried out in accordance with the test instruments that have been prepared. The result of this research is a Split Air Conditioner learning media tool that has dual functions, namely as a water heater and air conditioner. This simulation tool can operate properly and is able to heat 60 liters of water in 60 minutes with a hot water temperature of 42.5oC. The temperature resulting from the modification of the PK split Air Conditioner into a water heater has met the SNI 03-7605-2005 standard. This Air Conditioner modification can be used as a learning medium for students and lecturers to facilitate the learning process of the Air Conditioner (AC) Energy Conversion Machine course. In addition, this tool is already feasible as a practicum tool for the performance of dual-function air conditioners.AbstrakTujuan dari penelitian ini adalah untuk memodifikasi Air Conditioner Split PK untuk water heater dengan memanfaatkan panas buang kondensor yang dapat digunakan oleh mahasiswa Program Studi Teknik Mesin, Fakultas Teknik dan Ilmu Komputer Universitas Muhammadiyah Pontianak sebagai media pembelajaran di bidang mesin fluida dan mesin konversi energi skala laboratorium. Rancangan ini penting sebagai upaya untuk meningkatkan motivasi belajar, pemahaman, dan kemampuan berpikir mahasiswa dalam mata kuliah mesin konversi energi utamanya adalah air conditioner. Proses penelitian melibatkan perancangan, pembuatan, modifikasi, dan perakitan Air conditioner menjadi water heater menjadi satu kesatuan yang lengkap, serta pengujian alat untuk digunakan sebagai media pembelajaran. Pengumpulan dan analisis data dilakukan sesuai dengan instrumen uji yang telah disiapkan. Hasil penelitian ini adalah sebuah alat media pembelajaran Air Conditioner Split yang difungsikan ganda yaitu sebagai water heater dan pendingin ruangan. Alat simulasi ini dapat beroperasi dengan baik dan mampu memanaskan air sebanyak 60 liter dalam waktu 60 menit dengan temperatur air panas sebesar 42,5oC. Temperatur yang dihasilkan dari modifikasi Air Conditioner split PK menjadi water heater ini sudah memenuhi standar SNI 03-7605-2005 . Modifikasi Air Conditioner ini dapat dijadikan media pembelajaran bagi mahasiswa dan dosen untuk mempermudah proses pembelajaran mata kuliah Mesin Konversi Energi Air Conditioner (AC). Selain itu, alat ini sudah layak dijadikan alat praktikum unjuk kerja Air Conditioner yang difungsikan secara ganda.